Mental Health Professionals’ Views on the Regulation of Psychotherapy in Ontario - Vesely, Leslie M.; Smoliak, Olga; Gazzola, Nicola; Beaton, John (Canadian Journal of Counselling and Psychotherapy, 2023)
In Canada, mental health is regulated at the provincial level. In 2007, the Ontario government introduced the Psychotherapy Act (PA), which details the scope of practice as well as the controlled act of psychotherapy. The PA established the College of Registered Psychotherapists of Ontario (CRPO) to regulate its members in the service of protecting the public. Given the long history of contestation and ambiguity surrounding the definition of psychotherapy, the PA represents an important historic moment for practitioners in Ontario. However, little research has been conducted on psychotherapy practitioners’ experiences and perspectives on professional regulation. This study qualitatively explored perspectives on and experiences with the PA among regulated mental health practitioners who have access to the act of psychotherapy in Ontario, including psychotherapists, nurses, physicians, occupational therapists, psychologists, and social workers. The study provides insights into the ways that these professional groups are impacted by the regulation of psychotherapy and has implications for the future implementation of statutory regulation.